Insert L1 is a central hub for allosteric regulation of USP1 activity. (23rd February 2021) - Dharadhar, Shreya; van Dijk, Willem J; Scheffers, Serge; Fish, Alexander; Sixma, Titia K
Abstract: During DNA replication, the deubiquitinating enzyme USP1 limits the recruitment of translesion polymerases by removing ubiquitin marks from PCNA to allow specific regulation of the translesion synthesis (TLS) pathway. USP1 activity depends on an allosteric activator, UAF1, and this is tightly controlled. In comparison to paralogs USP12 and USP46, USP1 contains three defined inserts and lacks the second WDR20‐mediated activation step. Here we show how inserts L1 and L3 together limit intrinsic USP1 activity and how this is relieved by UAF1. Intriguingly, insert L1 also conveys substrate‐dependent increase in USP1 activity through DNA and PCNA interactions, in a process that is independent of UAF1‐mediated activation. This study establishes insert L1 as an important regulatory hub within USP1 necessary for both substrate‐mediated activity enhancement and allosteric activation upon UAF1 binding. Synopsis: Insert L1 of USP1 plays multiples roles in regulating USP1 activity. It contributes to inhibition that is relieved upon UAF1 binding and is important for interaction with DNA loaded PCNA. This region of USP1 could serve as a unique site to specifically target USP1 activity. UAF1 mediated activation of USP1 takes place by relieving the auto‐inhibition of USP1 Insert L1 and L3. USP1 activity is enhanced on DNA loaded PCNA‐Ub vs. free PCNA. Insert L1 of USP1 harbours DNA and PCNA recognition elements that are essential for increased USP1 activity on DNA loaded PCNA‐Ub. Abstract : Insert L1 of USP1 plays multiples roles in regulating USP1 activity. It contributes to inhibition that is relieved upon UAF1 binding and is important for interaction with DNA loaded PCNA.